Analisis Produksi Kentang Di Indonesia - Kristina Deta Karere; Dyanasari; A Yusuf Kholil (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
This study aims to analyze the development of potato production in Indonesia during the period of 1992–2023 and project its potential production up to 2050. The research employs descriptive analysis and the Average Annual Growth Rate (AAGR) calculation, using secondary data from FAOSTAT. The results indicate that Indonesia's potato production has fluctuated but shows a generally increasing trend. The increase is influenced by factors such as technology adoption, government policies, and rising domestic demand. Compared to Kenya, Indonesia still faces challenges in global competitiveness, particularly in seed quality and production costs. This study also proposes production improvement scenarios through cultivation efficiency and sustainable policy support. The findings are expected to serve as a reference for the development of national potato production to strengthen food security and futureexpor prospects. Keywords: Potato production, AAGR, Indonesia, Kenya, agricultural policy.